Pós-verdade: um sintoma social analisado a partir da teoria dos discursos de Lacan - Vigar, Vivian Valerie Carol Ann (2023)
The general objective of this work is to investigate, through Psychoanalysis, what in our culture we call "post-truth" and which, in the present research, from the field in which we are inserted, we defend as a social symptom, whose effects are perceived in the subject and in the social bond, mainly through fake news. Thus, in order to place post-truth in the field of Psychoanalysis, it was necessary to demarcate its causes and effects, tracing the difference between, on the one hand, the most direct manifestations of post-truth, fake news, and on the other hand, some subjective phenomena linked to religious and ideological beliefs, scientific denialism, historical revisionism and conspiracy theories, which end up underpinning post-truth. In general, post-truth is fostered by narratives and reports that confuse the discernment between the false and the true, harming decision-making concerning the public sphere. Thus, we understand that, supported by the presupposition of freedom of expression, post-truth is a symptom that supposes the lack of responsibility of speech, bearing the voice of the injunction to jouissance, of the imperative search for satisfaction of pleasure in the social field, and becoming a problem for the human endeavor towards the progress of civilization in opposition to barbarism. Having as main instrument of investigation the theory of discourses, formulated by Jacques Lacan and supported by psychoanalysts authors who, together with Sigmund Freud, support the equivalence of individual psychology to social psychology, we seek to make a reading through psychoanalytic concepts and overdeterminations. symbolic and imaginary that aim to buffer the real of the social bond with lies and absurdities. Finally, we conclude that post-truth is a social symptom closely linked to the ideology of neoliberal capitalism and aims, through the promise of continuous enjoyment, in order to abolish class struggle, perpetuating relations of domination and exploitation and maintaining the population subservient to the laws of the market